Impatiens tanintharyiensis, a new record of Impatiens sect. Semeiocardium (Balsaminaceae) for Thailand - Ruchisansakun, Saroj; Suksathan, Piyakaset; Triboun, Pramote; Sinrothanakorn, Chalit (Thai Forest Bulletin (Botany), 2021)
Impatiens tanintharyiensis (Balsaminaceae) is reported in Thailand for the first time from a population in Ngao Waterfall National Park, Ranong Province. This population differs from that at the type locality in Myanmar by having smaller, purple flowers (vs bigger purplish-pink flowers). An expanded description of this taxon and colour photographs are provided.